Geotecnologias aplicadas à análise do assoreamento de reservatórios de hidrelétricas em cenário de escassez de dados de séries históricas - Catelani, Celso de Souza [UNESP] (2015)
Knowledge about potential sediment production is essential for the feasibility analysis to implement a Small Hydropower Plant (PCH, in Portuguese) for long term efficient operation. This study was developed in the PCH Costa Rica (MS) watershed, with approximately 1,200 km² that has limited historical series of hydrological and hydrosedimentological data what make reliable estimations and replication of results difficult. This study aimed to predict the potential soil loss and sediment yield using a model based on the software Soil and Water Assessment Tool (SWAT) and Geographic Information Systems (GIS) techniques. The results showed that the PCH Costa Rica watershed has a high potential to produce sediments, with total amount reaching 1,049,522 Mg year-1, corresponding to 8.43 Mg ha-1 yr-1 and a continuous loss of soil layer of 0.0566 mm yr-1. SWAT modeling and geo-technologies were efficient in the evaluation and quantification of potential soil loss and sediment production in this watershed, even in a scenario of limited data. Modeling watershed using SWAT resulted in strong positive range (above 0.6) of Pearson correlation between simulated and observed values and moderate positive values (0.3 to 0.6) for the calibration and validation, respectively. This allows quantitative estimations of sediments generated in the watershed and identification of sub-basins with higher rates of sediment production by modeling. The assessment of changes in land use between 1984 and 2011 showed that in addition to the natural vulnerability of physical environment, the conversion of Savannah vegetation to agricultural use, without conservation practices, increased the erosion rates in recent decades, compromising the performance of PCH Costa Rica for energy production